Comparative Effectiveness of Interventions for Global Cognition in Patients With Mild Cognitive Impairment: A Systematic Review and Network Meta-Analysis of Randomized Controlled Trials - Xu, Zijun; Sun, Wen; Zhang, Dexing; Chung, Vincent Chi-Ho; Sit, Regina Wing-Shan; Wong, Samuel Yeung-Shan (Frontiers in Aging Neuroscience, 2021)
Background: There is a lack of study comprehensively comparing the effects of all existing types of interventions on global cognition among patients with mild cognitive impairment (MCI). Aims: To conduct a network meta-analysis to evaluate the effectiveness of different types of interventions in improving global cognition among MCI patients. Methods: Randomized controlled trials (RCT) assessing the effects of pharmacological or non-pharmacological interventions on the Mini-Mental State Examination (MMSE) in MCI patients were included. Two authors independently screened the studies and extracted the data. Random-effects network meta-analysis was used to synthesize the data. Results were summarized as mean difference (MD) and corresponding 95% confidence intervals (CI) of MMSE in forest plots. Results: Fifty RCTs with 5944 MCI patients met the inclusion criteria and 49 were included in the network meta-analysis. Compared with the control group, cognition-based intervention (MD=0.80, 95% CI 0.04 to 1.57), physical exercise (MD=1.92, 95% CI 1.19 to 2.64), combined physical exercise and cognition-based intervention (MD=1.86, 95% CI 0.60 to 3.12), and antioxidants (MD=0.94, 95% CI 0.04 to 1.83) had positive effects on MMSE in participants with MCI. There was no significant difference between all other interventions included and the control group. Conclusions: This study suggested that cognition-based intervention, physical exercise, combined physical exercise and cognition-based intervention, and antioxidants could be among the most effective interventions on global cognition in older adults with MCI. The availability, acceptability, and cost-effectiveness of interventions should also be taken into consideration when selecting interventions. Registration: PROSPERO CRD42020171985.